Effectiveness of sofosbuvir/pegylated-interferon plus ribavirin in treatment of hepatitis C virus genotype 4 patients - Abdel-Moneim, Adel (Clin Exp Hepatol, 2018)
INTRODUCTION: New regimens involving direct-acting antiviral agents (DAAs) have recently been approved for the treatment of hepatitis C virus (HCV) genotype 4 (GT4). The current study aims to assess the efficacy and safety of sofosbuvir (SOF) with pegylated interferon (PegINF)/ribavirin (RBV) for chronic HCV GT4 patients at the beginning of the interferon-free era. MATERIAL AND METHODS: Between March 2015 and November 2015, 99 patients (59 naïve and 40 experienced) infected with HCV GT4 were enrolled in the study. Eligible patients received daily oral 400 mg SOF, RBV (body weight: < 75 kg, 1000 mg; < 75 kg, 1200 mg), the dose modified according to patient tolerability, plus 180 μg PegINFα-2 once weekly for 12 weeks. RESULTS: Among the patient cohort, sustained virological response 12 weeks after the end of treatment (SVR12) was achieved by 88% (87/99) of all patients, by 93% (55/59) of naïve patients and by 80% (32/40) of experienced patients. Regarding treatment failure, the data recorded 12% (12/99) of patients (4 null responses and 8 relapsers). Otherwise, the most common adverse events observed during the study included headache, nausea, fatigue, dyspnea, influenza-like illness, anemia, and leukopenia. CONCLUSIONS: SOF combination-based therapies were considered promising choice regimens for chronic HCV infection. The present findings suggest that the combination of the SOF/PegINF/RBV regimen was effective for Egyptian patients with HCV GT4. The recorded adverse events and viral outcome revealed the high need for further efforts to minimize the side effects of the current regimen and/or replace PegINF with additional potent DAA(s) to increase SVR12 to achieve 100%.